Graduating the poorest into microfinance : linking safety nets and financial services - Hashemi, Syed (CGAP WashingtonUS, 2006)
Explores a few cases where the poorest participate in grant-funded safety net programmes, where they receive nonfinancial support, as well as support to graduate from their existing levels of poverty to a level where they can make good use of access to appropriate financial services.